Analysis of Hazard Area of Dispersion Caused by Leakage from Underground Gas-Storage Caverns in Salt Rock - Ya Yang; Shigang Yang; Zhan Li; Qin Fang; Jianhua Wu; Jiongwei Cai; Wensheng Sun (Advances in Civil Engineering)
To provide information concerning quantitative risk analysis of gas-storage caverns, it is vital to estimate the hazard area of dispersion caused by accidental leakage. The Gaussian plume model is selected to calculate the hazard area caused by continuous leakage; the method of analysis is validated using wind-tunnel experiments of acetylene. Fluent is used to simulate the hazard area of dispersion caused by instantaneous leakage; the method of numerical simulation is verified by Burro/Coyote trials. Furthermore, a sample underground gas-storage cavern in salt rock is examined with respect to the toxic threshold limit value and the upper and lower flammability limits. In doing so, the factors that influence the hazard range of dispersion from salt cavern are discussed. The results indicate that the hazard area decreases with an increase in wind speed and a decrease in atmospheric stability when the leakage is continuous. However, the hazard area decreases with a decrease in wind speed when leakage is instantaneous.